2018
DOI: 10.1530/erc-17-0051
|View full text |Cite
|
Sign up to set email alerts
|

GLUT12 promotes prostate cancer cell growth and is regulated by androgens and CaMKK2 signaling

Abstract: Despite altered metabolism being an accepted hallmark of cancer, it is still not completely understood which signaling pathways regulate these processes. Given the central role of androgen receptor (AR) signaling in prostate cancer, we hypothesized that AR could promote prostate cancer cell growth in part through increasing glucose uptake via the expression of distinct glucose transporters. Here, we determined that AR directly increased the expression of , the gene that encodes the glucose transporter GLUT12. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 63 publications
9
37
1
Order By: Relevance
“…TBC1D4 may not be exclusively involved in GLUT4 vesicle traffic as it has been recently shown to participate in the cell surface expression of GLUT12 in response to activation of calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2) and AMPK signaling [253]. Likewise, overexpression of phospho-site mutants of TBC1D1 and TBC1D4 was reported to reduce cell surface expression of GLUT1 in non-insulin target cells [90].…”
Section: Glut12: Compensatory Glucose Transporter Upon Glut4 Deficienmentioning
confidence: 99%
“…TBC1D4 may not be exclusively involved in GLUT4 vesicle traffic as it has been recently shown to participate in the cell surface expression of GLUT12 in response to activation of calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2) and AMPK signaling [253]. Likewise, overexpression of phospho-site mutants of TBC1D1 and TBC1D4 was reported to reduce cell surface expression of GLUT1 in non-insulin target cells [90].…”
Section: Glut12: Compensatory Glucose Transporter Upon Glut4 Deficienmentioning
confidence: 99%
“…It is important in foetal development, particularly of the heart, while GLUT12 deficiency is associated with heart failure [ 105 ]. GLUT12 expression is upregulated by androgens in the prostate and levels are increased in prostate cancers [ 10 , 39 , 224 ].…”
Section: Class 3: Gluts 6 8 10 12 and Glut13 (Htmi)mentioning
confidence: 99%
“…We also wish to acknowledge prior work from Wang and colleagues that demonstrated that androgens could increase the expression of SLC1A4 and SLC1A5 in LNCaP cells and their expression was increased in prostate cancer patient samples (7,8). It is true that similar data for SLC1A5 (alongside our mined SLC1A4 clinical data) were presented in Dr. Holst's 2015 study (7), but it was unintentional as evidenced from our published work on unrelated topics (9) including work done by us well before any of these studies (10), demonstrating that this is a common format we use to present these types of clinical data. Importantly, while our study further validates the work of Wang and colleagues that defined the functional importance of SLC1A5/ASCT2 in prostate cancer (7,8), there were some important differences.…”
mentioning
confidence: 73%